2015
DOI: 10.1002/jcp.24839
|View full text |Cite
|
Sign up to set email alerts
|

Role of Methionine Adenosyltransferase α2 and β Phosphorylation and Stabilization in Human Hepatic Stellate Cell Trans‐Differentiation

Abstract: Myofibroblastic trans-differentiation of hepatic stellate cells (HSCs) is an essential event in the development of liver fibrogenesis. These changes involve modulation of key regulators of the genome and the proteome. Methionine adenosyltransferases (MAT) catalyze the biosynthesis of the methyl donor, S-adenosylmethionine (SAMe) from methionine. We have previously shown that two MAT genes, MAT2A and MAT2B (encoding MATα2 and MATβ proteins respectively), are required for HSC activation and loss of MAT2A transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…17 This method was used to separate phosphorylated and nonphosphorylated UBC9 proteins as distinct bands of different mobilities. SDS-PAGE gels (10%) containing manganese chloride and 15 mmol/L phos-tag were prepared according to previously described protocols 17 using total liver extracts or RAW264.7 cell extracts.…”
Section: Phos-tag Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…17 This method was used to separate phosphorylated and nonphosphorylated UBC9 proteins as distinct bands of different mobilities. SDS-PAGE gels (10%) containing manganese chloride and 15 mmol/L phos-tag were prepared according to previously described protocols 17 using total liver extracts or RAW264.7 cell extracts.…”
Section: Phos-tag Analysismentioning
confidence: 99%
“…Equal amounts of phosphorylated or unphosphorylated protein fractions were immunoprecipitated with two micrograms of UBC9 antibody, according to previously published protocols, 13,17 and then immunoblotted with Ikba antibody.…”
Section: Phospho-affinity Purification Chromatography and Coimmunoprementioning
confidence: 99%
“…40 The phosphorylation of both MATα2 and MATβ is strongly induced during HSC activation. 41 Phospho-MATα2 and MATβ proteins are highly stable and the mutation of specific phosphorylation sites (Y371/Y374 in MATα2 and T257/Y259 in MATβ) inhibits HSC activation. 41 Chemical inhibitors, gene silencing and in vitro kinase assays have shown that mitogen-activated protein kinase/ERK kinase (MEK) might be involved in MATα2 phosphorylation whereas extracellular signal-regulated kinase (ERK) might phosphorylate the MATβ protein.…”
Section: Methionine Adenosyltransferasesmentioning
confidence: 99%
“…41 Chemical inhibitors, gene silencing and in vitro kinase assays have shown that mitogen-activated protein kinase/ERK kinase (MEK) might be involved in MATα2 phosphorylation whereas extracellular signal-regulated kinase (ERK) might phosphorylate the MATβ protein. 41 …”
Section: Methionine Adenosyltransferasesmentioning
confidence: 99%
“…Antibodies used for Western blotting were: PHB1 and IGF2 (Abcam, Cambridge, MA), CTCF (Cell Signaling, Danvers, MA), and actin control (Sigma). For co-immunoprecipitation, 500 g of radioimmunoprecipitation assay extracts of cells or tissues were immunoprecipitated with 2 g of PHB1 antibody and immunoblotted with CTCF antibody according to previously established protocols (26). Western blots were developed using the chemiluminescence ECL system (Amersham Biosciences).…”
Section: ϫ⌬⌬Ctmentioning
confidence: 99%